Checklist based reading's influence on a developer's understanding - McMeekin, David; Von Konsky, Brian; Chang, Elizabeth; Cooper, David (Institute of Electrical and Electronics Engineers (IEEE) - Computer Society, 2008)
This paper addresses the influence the Checklist Based Reading inspection technique has on a developer's ability to modify inspected code. Traditionally, inspections have been used to detect defects within the development life cycle. This research identified a correlation between the number of defects detected and the successful code extensions for new functionality unrelated to the defects. Participants reported that having completed a checklist inspection, modifying the code was easier because the inspection had given them an understanding of the code that would not have existed otherwise. The results also showed a significant difference in how developers systematically modified code after completing a checklist inspection when compared to those who had not performed a checklist inspection. This study has shown that applying software inspections for purposesother than defect detection include software understanding and comprehension.